Together we stand? Belonging motive moderates the effect of national ingroup salience on attitudes towards ethnic minorities. (July 2020) - Adam-Troian, Jais; Çelebi, Elif; Bonetto, Eric; Taşdemir, Nagihan; Yurtbakan, Taylan
Abstract: Common ingroup categorization reduces outgroup prejudice. This link is moderated by distinctiveness motives (i.e., individuals perceiving this identity as too inclusive). Yet, Optimal Distinctiveness Theory states that both distinctiveness and belonging motives shape intergroup attitudes. For the first time we tested the hypothesis that belonging and distinctiveness motives jointly moderate common ingroup categorization effects. Using a flag-priming paradigm, two studies showed that, when national ingroup identity was salient, only belonging motives predicted positive attitudes towards outgroups (Study1: Syrians in Turkey, N = 184; Study 2: Maghrebis in France N = 151). This was corroborated by sensitivity analyses on aggregated data ( N = 335). These results suggest that national identification may lead to positive outgroup attitudes for individuals who derive belonging from it.